A comparative study of physical parameters of selected ketorolac tromethamine tablets available in the pharma market of Bangladesh - Nishat Nasrin, Muhammad Asaduzzaman, Rumana Mowla, Farhana Rizwan, Ashiqul Alam (Journal of Applied Pharmaceutical Science)
Quality of pharmaceutical product is very important because drugs must be marketed as safe and therapeutically active formulations whose performance is consistent and predictable. The evaluation of the physical characteristics of the pharmaceutical products can ensure their quality as well as bioavailability and impart optimum therapeutic activity. Ketorolac tromethamine was chosen for this comparative study because this drug is widely used worldwide for treating moderate to severe pain. The present study compared the weight variation, hardness and the abrasion withstanding ability of eight brands of Ketorolac tromethamine tablets marketed in Bangladesh following USP guidelines. All eight brands of Ketorolac tromethamine tested conformed to the USP weight variation test. All the brands had average hardness of =3 kg which was satisfactory for immediate release tablet like ketorolac tromethamine. All the brands had shown their friability variation within ±1% range specified by USP. Standard deviation was calculated among all the brands which was very close to individual percentage friability of all the brands. All the brands of ketorolac tromethamine complied with USP requirements of physical quality parameters. It follows that these brands will show good disintegration and dissolution profile which would further help in achieving optimum bioavailability and in fulfilling the patient demands.
Keywords: Ketorolac tromethamine, weight variation, hardness, friability, USP.